2015
DOI: 10.4269/ajtmh.14-0837
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Blomia tropicalis Allergen Blo t 5 in Cereal and Cereal-Based Foods Consumed in the Nile Delta, Egypt

Abstract: Abstract. The mite Blomia tropicalis has significant prevalence worldwide. Blo t 5 is a major B. tropicalis allergen that has been associated with sensitization and allergic symptoms in many asthmatic patients. Besides house dust, contaminated foodstuffs are an important source of exposure to B. tropicalis allergens. In this study, a double sandwich enzyme-linked immunosorbent assay (ELISA) using mAb 4D4 and biotinylated mAb 4G9 was done to detect Blo t 5 allergen in different types of raw and processed foods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Oral mite allergy and anaphylaxis is increasingly detected in some African nations. Blo t 5, which is a major Blomia tropicalis mite allergen was detected in several raw and processed food samples collected from retail stores in the Nile Delta of Egypt including wheat, corn, rice, bean, wheat and corn flour, cake, and rusk 62 …”
Section: Food Allergensmentioning
confidence: 99%
“…Oral mite allergy and anaphylaxis is increasingly detected in some African nations. Blo t 5, which is a major Blomia tropicalis mite allergen was detected in several raw and processed food samples collected from retail stores in the Nile Delta of Egypt including wheat, corn, rice, bean, wheat and corn flour, cake, and rusk 62 …”
Section: Food Allergensmentioning
confidence: 99%
“…House dust mites are by far the most predominant allergen sources in the Tropics where populations are perennially exposed, mainly to B. tropicalis and D. pteronyssinus [ 238 ]. Since it thrives in warm and humid climates, B. tropicalis is an important allergen in tropical and subtropical regions [ 13 , 59 , 239 – 241 ]. The HDM fauna in Los Baños, Laguna, Philippines included 32 species of mites belonging to 7 families.…”
Section: Introductionmentioning
confidence: 99%
“…Samples of house dust collected from 50 homes in El-Arish city, North Sinai, Egypt, revealed that 34.6 % of the samples had mites [ 243 ]. Blo t 5 allergen was detected in 34 out of 88 raw and processed food samples including wheat, corn, rice, bean, wheat and corn flour, cake, and rusk collected from retail stores in Benha city in the Nile Delta of Egypt [ 241 ]. In some tropical areas, the majority of the homes from mite allergic patients with asthma and/or rhinitis present concentrations of group 1 allergens >10 μg/g of dust in at least one site of the house [ 244 246 ].…”
Section: Introductionmentioning
confidence: 99%
“…To distinguish between true cosensitization and cross-reactivity between B. tropicalis and other mites, it would be important to include more specific allergens to the common diagnostic platforms [93]. An ELISA kit for quantification of Blo t 5 in environmental samples or Blomia extracts is available from Indoor Biotechnologies [2,12,94]. …”
Section: Diagnosis and Immunotherapy Of B Tropicalismentioning
confidence: 99%